Peningkatan Kesehatan Orang dengan Gangguan Jiwa (ODGJ) melalui Posyandu Jiwa dengan Kearifan Lokal: Yoga Bali di Desa Ketewel - Ni Made Sri Muryani; Ni Putu Eka Febianingsih; I Gusti Bagus Wirawan; I Gede Yudiana Putra (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2026)
Background: Ketewel Village has formed a Mental Health cadre for the Mental Health Posyandu, but implementation has not been effective because the cadres have not received training, and the community remains reluctant to use the mental health posyandu services. The aim of this service activity is to increase cadres' knowledge and family visits to Posyandu Jiwa. Method: Posyandu Jiwa Ketewel Village with a cadre of 10 people. This activity method involves providing training and pre- and post-tests to assess the cadres' understanding. Results: Increased knowledge of cadres, previously obtained a score of 56 – 74% in the sufficient category, and after training, an increase in cadre knowledge was obtained, namely with a score of ³ 75% in the good category. There has been an increase in the number of visits to mental health posyandu, where previously less than 50% of ODGJ attended the mental health posyandu, and when the mental health posyandu was implemented with Yoga Bali, it was found that 85% of ODGJ attended. Conclusion: Increasing cadres' knowledge and increasing the number of visits to mental health posyandu.